Long-term asymmetric impacts of insecurity and corruption on development of tourism: Evidence from Nigeria - Nurudeen Abu (Revista Galega de Economía)
This research evaluates the long-term asymmetric impacts of insecurity and corruption on the development of tourism in Nigeria using a non-linear ARDL (NARDL) method to analyze quarterly data for the 1996-2021 period. The cointegration test result provides an evidence of a long-term relationship among these three variables (corruption, insecurity and tourism development), along with exchange rate, income and infrastructure. The asymmetry test results reveal asymmetry between tourism development and both corruption and insecurity. The outcomes of the empirical exercise indicate that a positive shock to control of corruption (decline in corruption) fosters long-term tourism development, while a negative shock to control of corruption (increase in corruption) does not significantly explain long-term tourism development. In addition, a positive change in government expenditure on internal security (increase in internal insecurity) lowers long-term tourism development, but a negative change in government spending on internal security (decrease in internal insecurity) enhances long-term tourism development. Depreciation of the domestic currency promotes long-term tourism development. Thus, policies that reduce corruption and insecurity are recommended to promote long-term development of the tourism sector in Nigeria.